From the Pantheon to the Anthropocene: Introducing Resilience in Architectural History. Issue 1 (12th June 2019) - Merrill, Elizabeth Mays; Giamarelos, Stylianos
Abstract : Originally developed in the ecological circles of the 1970s that pursued critical alternatives to the modernist worldview, the concept of 'resilience' has pervaded 21st-century thought, from psychology to political theory, and from planning to architecture. But in most of its current guises, it has been used in positivist and future-oriented frames of thinking that limit it to an aspired benchmark for managing crises and withstanding catastrophic events. This Special Collection of Architectural Histories is an attempt to recuperate the overlooked potential of 'resilience' by asking whether and how its introduction in architectural history can transform current disciplinary practices. In their articles, the contributing authors revisit buildings that have been reused and transformed to withstand change over the centuries. Adopting the long-term perspective of 'resilience', they examine these physical objects as carriers of multiple layers of interventions, leading them to re-evaluate the intentions of architects and users and to reconsider the place of these buildings in architectural history. In most cases, 'resilience' offers a novel historiographical perspective that unveils long-standing conceptual schemata, from periodizations to methodological tropes, which still condition the historians' interpretation of the past. In the final instance, 'resilience' illuminates the deep-seated modernist dichotomy between 'innovation' and 'tradition' in architectural history. In keeping with its origins in the late 20th-century, the concept offers a significant alternative to 21st-century architectural historians' established views on modernity that are still embedded in their thought and practice.